Time series clustering of online gambling activities for addicted users’ detection - Peres, Fernando (2021)
Peres, F., Fallacara, E., Manzoni, L., Castelli, M., Popovič, A., Rodrigues, M., & Estevens, P. (2021). Time series clustering of online gambling activities for addicted users’ detection. Applied Sciences (Switzerland), 11(5), [2397]. https://doi.org/10.3390/app11052397